Non-invasive management of severe red blood cell alloimmunization during pregnancy. (May 2023) - Di Ilio, Chiara; Dall'Asta, Andrea; Degennaro, Valentina Anna; Re, Francesca; Incontri, Arianna; Celora, Gabriella Maria; Melandri, Elena; Soli, Maurizio; Ghi, Tullio
Highlights: Intrauterine Transfusion (IUT) is the gold standard treatment for fetal anemia. Serial IUT procedures are often required in severe alloimmunization, and the incidence of procedure-related complications is higher for IUT performed prior to 20 weeks. The combination of plasmapheresis and intravenous immunoglobulins administration is a reliable option for a non-invasive management of severe anti-D alloimmunization.